Normative Values for the Voice Handicap Index-10 - Arffa, Rachel E.; Krishna, Priya; Gartner-Schmidt, Jacqueline; Rosen, Clark A. (Journal of voice, 2012)
The objective of this study was to elucidate the normative values for the Voice Handicap Index-10 (VHI-10) questionnaire. VHI questionnaires were completed by 190 subjects without voice complaints. The results were then analyzed for mean, standard error of the mean (SEM), and standard deviation (SD) for both the original VHI and VHI-10 subset questionnaires. Outliers were defined as being more than three standard deviations above the mean. Analysis of 156 VHI questionnaires revealed a mean of 6.86 (SEM=0.79, SD=9.88) for the normative values. One hundred fifty-eight VHI-10 questionnaires were analyzed to show a mean of 2.83 (SEM=0.31, SD=3.93) for the normative values. This study offers normative data for the VHI-10 that has been missing in the literature. A VHI-10 score >11 should be considered abnormal.